Studi Komparasi Implementasi dan Tantangan Kebijakan Otonomi Daerah di Sumatera dan Papua - Jamaluddin, Jamaluddin; Al Syahrin, M Najeri (Universitas Muhammadiyah Sorong, 2024)
The purpose of this article is to analyze the implementation of regional autonomy policy by taking the case of comparison between the islands of Sumatra and Papua. The research method uses the literature study method to collect various information relevant to the qualitative approach. This approach is considered appropriate because the implementation of regional autonomy is multi-dimensional. The implementation of regional autonomy in Sumatra and Papua over the past two decades has not been able to significantly improve welfare, especially in reducing poverty and improving education, health, and economic infrastructure. The success rate of implementing regional autonomy in the Sumatra region from the aspect of regional competitiveness is 18.30% and has not been successful enough to increase regional competitiveness in terms of GDP per capita. In addition, the implementation of regional autonomy mainly in conflict areas, the level of conflict in Aceh decreased significantly after regional autonomy was enacted. From an average of 1,500 deaths per year in the period 1999-2005 to an average of 50 deaths per year in the period 2006-2018. While the level of conflict in Papua increased significantly after regional autonomy was imposed, from an average of 100 deaths per year in the period 1999-2005 to an average of 300 victims killed per year in the period 2006-2018. In Sumatra, particularly in Aceh, regional autonomy is successful because it involves the participation and consensus of all parties involved, including former rebels, civil society, and the central government. In Papua, regional autonomy fails because it is carried out unilaterally and authoritatively by the central government, without regard for the interests and rights of the Papuan people.